Front Cover: Study of Six Green Insensitive High Energetic Coordination Polymers Based on Alkali/Alkali‐Earth Metals and 4, 5‐Bis(tetrazol‐5‐yl)‐2 H‐1, 2, 3‐triazole (Chem. Asian J. 24/2017). Issue 24 (4th December 2017) - Chen, Dong; Jing, Dong; Zhang, Qi; Xue, Xianggui; Gou, Shaohua; Li, Hongzhen; Nie, Fude
Abstract : The front cover indicates that constructing green insensitive high‐performance energetic coordination polymers (ECPs) with alkali/alkali‐earth metal ions (Na(I), Cs(I), Ca(II), Sr(II), Ba(II)) and a nitrogen‐rich organic backbone is a feasible strategy. Six diverse dimensional ECPs possess outstanding energy density and low sensitivity, excellent thermal stability and pyrotechnic effect. As the structural reinforcement increases from 1D to 3D, these properties improve significantly, supporting the usefulness of this strategy for the preparation of insensitive highly energetic materials. More information can be found in the Full Paper by Qi Zhang et al. onpage 3141 in Issue 24, 2017 (DOI:10.1002/asia.201701052 ).